Semi-Batch Reactive Distillation of Consecutive Reaction : The Saponification Reaction of Diethyl Adipate with Sodium Hydroxide Solution (Journal of Engineering, 2016)
This research presents a new study in reactive distillation by using consecutive reaction: the saponification reaction of diethyl adipate (DA) with sodium hydroxide solution .The effect of three parameters were studied through a design of experiments applying 23 factorial design . These parameters were : the mole ratio of DA to NaOH solution (0.1 and 1) , NaOH solution concentration (3 N and 8 N) , and batch time (1.5 hr. and 3.5 hr.) . The conversion of DA to sodium monoethyladipate(SMA)(intermediate product) was the effect of these parameters which was detected . Also , the percentage purity of the intermediate product was recorded . The results showed that increasing mole ratio of DA to NaOHsolution increases the conversion and percentage purity to a maximum value within the range of study . The effect of NaOH solution concentration decreases the conversion and percentage purity to specified value within the range of study . The effect of batch time on conversion and percentage purity , when NaOH solution concentration (3 N) is as follows : the increasing in batch time decreases the conversion and percentage purity to specified value within the range of study . When NaOH solution concentration (8 N) increasing batch time decreases the conversion , while percentage purity increases with increasing batch time to a maximum value within the range of study . The maximum attainable conversion within the studied range of parameters was  eighteen fold of the base case , while the maximum percentage purity was (99.40 %) .Empirical equation was obtained using statistical analysis of experimental results . The empirical results of relative conversion was drawn . The empirical graphs showed linear variation .